The Effect of Artificial Intelligence and Chatbot on Consumer Satisfaction of Shopee platform users in Medan City - Ami Natuz Zahara; Ari Prabowo; Etty Sri Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the impact of the use of artificial intelligence (AI) and Shopee's chatbot on consumer satisfaction of the Shopee e-commerce platform in Medan. The research method uses a quantitative approach with data collection techniques through online surveys of 120 active Shopee users. The regression analysis results show that AI and Shopee chatbot have a positive and significant impact on customer satisfaction (p < 0,000). The ease of use features, response speed, and information accuracy of chatbots are key factors contributing to increased consumer satisfaction. The implications of this research provide insight into the development of AI technology in improving customer service in the e-commerce industry.